Pelatihan Penggunaan Alat AL Sintan Pertanian Cultivator Di Petani Labuhanbatu Desa Kampung Baru - Anggana, Zelvin; Sepriani, Yusmaidar; Lestari, Widya; Rizal, Khairul (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Cultivator is a piece of agricultural machinery and equipment used to cultivate secondary land. This service aims to provide information on the use of al-sintan Cultivator agricultural tools to the community. The implementation strategy used in this service is a traditional, one-on-one methodology. In explaining the theory regarding agricultural al-sintan instruments, Culltivator uses classical methods. Meanwhile, an individual approach is taken during training. The explanation of the stages of implementing service is as follows; Identification of problems, Preparation of activity plans, Training and counseling, Field demonstrations.